Effect of Diet, Insulin and Exercise on the Regulation of Carbohydrate Metabolism in Health and Type 1 Diabetes - Chokkalingam, Kamalakkannan (2007)
The objective of this thesis was to further the understanding of the effect of diet, insulin and exercise on the regulation of carbohydrate metabolism in health and type 1 diabetes. Three studies were undertaken in both non-diabetic healthy volunteers and patients with type 1 diabetes. The first study determined the influence of high fat diet on biochemical and molecular regulators of whole body and muscle metabolism in healthy volunteers. The second study examined the influence of insulin on whole body and muscle metabolism in patients with type 1 diabetes during moderate exercise. The final study compared the influence of insulin and a high carbohydrate diet on liver glycogen concentrations and substrate oxidation during exercise between patients with type 1 diabetes and healthy volunteers.